Educational demands of family members of children with special health care needs in the transition from hospital to home - Meirilane Lima Precce; Juliana Rezende Montenegro Medeiros de Moraes; Sandra Teixeira de Araújo Pacheco; Liliane Faria da Silva; Daniele Santos da Conceição; Elisa da Conceição Rodrigues
ABSTRACT Objectives: to analyze the educational demands of family members of children with special health care needs in the transition from hospital to home Methods: qualitative research conducted between February and June 2018, using the handbook on creativity and sensitivity dynamics, from the sensitive creative method; the participants were nine family caregivers of children admitted to a public hospital in Rio de Janeiro; the data were subjected to French discourse analysis Results: the educational demands were clinical, centered on the categories complex and continuous care, technological care, modified habits, medication, development and mixed care, and social, related to the supplies and rights of children Final Considerations: the social educational demand has emerged as a new demand to be incorporated in the care of these children. The transition from hospital to home should be progressive and have the nurse as its coordinator, with the objective of providing participatory, safe, quality care, articulated within a social network